Students’ Perception on the Integration of Video Recording Assignments in Speaking Courses - Komang, Dwi Krisna (English Education Department - Universitas Nasional Karangturi, 2025)
This study explores students’ perceptions of using video recording assignments in EFL speaking classes, focusing on their influence on students’ confidence, motivation, and learning outcomes. Using a descriptive quantitative method, data were gathered from 30 fourth-semester English Education students at UHN I Gusti Bagus Sugriwa Denpasar through a Likert-scale questionnaire. Findings indicate that the majority of students have a positive perception of video recording tasks. They reported increased comfort, confidence, and fluency when speaking English via video compared to in- class speaking. Students also found video recordings helpful for identifying speaking mistakes and improving performance. However, some challenges were noted, particularly technical issues and the time-consuming nature of video production. While most students acknowledged the benefits, opinions were mixed about whether such tasks should continue in future classes. These findings suggest that while video assignments can enhance speaking skills and learner autonomy, practical barriers need to be addressed for their effective implementation.